Participation Of Tribal Farm Women In Breeding, Feeding And Management Practices Of Milch Animals Of Tapi District Of South Gujarat, India - Pandya, C.D.; Raval , J.K.; Soni, Arti N. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Women play an important role in this sector. In India, women contribute 71 per cent of the total participation in livestock sector. Though agriculture as a whole and dairy in specific, the farm women play a vital responsibility. So, the present study was carried out specific objective to know the participation of farm women in feeding, breeding and management practices. The study was undertaken in Tapi district of Gujarat state in the year 2011. All the ten adopted villages of the Krishi Vigyan Kendra, Vyara were selected purposively for the study. From each village, 20 respondents were selected making total sample size 200. The structural interview schedule was prepared. The statistical measures namely frequency, percentage, mean were used. It could be concluded that the respondents were taking regular participation in activity of selection of type of the milch animals, taking participation in activity of Purchase of improved / cross breed animals on regular basis, taken participation in activities like bringing fodder, have daily participation in giving warm water to bath at calving, taking contribution in feeding colostrums to the calf, adopting veterinary aids like vaccination, have revealed their contribution in activities like watering at proper time to animals, have revealed their stack in activities of purchase of feed / fodder, selling of milk through cooperative society, cleaning milk vessels, have contribution in making milk products like curd.